Magnetic separation of nickel-plating waste liquid using a high temperature superconducting bulk magnet. (1st September 2022) - Oka, T; Sudo, K; Dadiel, J L; Sakai, N; Seki, H; Miryala, M; Murakami, M; Nakano, T; Ooizumi, M; Yokoyama, K; Tsujimura, M
Abstract: Ni is one of the important metal resources. Because Ni-containing waste liquid is drained after several plating turns in the factories, an effective recycling technique should be developed. A unique magnetic separation technique using high temperature superconducting bulk magnet has succeeded in collecting Ni-sulfate crystals, which were fabricated from the Ni-plating waste liquid. Pulsed-field magnetizing method was employed to activate the bulk magnet up to 2.80 T, which produced a field space of 1.40 T on the surface of the waste channel. Green coarse crystals were attracted from the flowing stream of Ni-saturated liquid containing weakly-magnetic particles of Ni-compounds. The magnetically-collected particles were identified as paramagnetic NiSO4 /6H2 O crystals, and slight differences in Ni concentration and grain size were observed between the particles attracted and not-attracted to the 1.8 T magnetic pole. In both cases, the large grains were found to consist of a single phase. The compound can be used as a raw material in the Ni-recycle process. This preferential extraction suggests a novel recycling method of Ni resource.